Auditoría De Cumplimiento Al Proceso Tributario Y Su Incidencia En Las Obligaciones Impositivas De La Empresa Agrícola Guamán, Cantón Valencia. Año 2023 - Vargas Quilumba, Erika Vanessa (2025)
This research work is based on the execution of a compliance audit of the tax process and its impact on the tax obligations of the company Agrícola Guamán, year 2023, the problem of the study is to evaluate how the compliance audit in the tax process affects the tax obligations. To fulfill the specific objectives, the level of compliance with tax regulations and tax obligations was verified through efficiency indicators, the consistency of the information in the tax return forms was also analyzed, and finally, the effectiveness of the internal control of the tax process was determined through the COSO I model. The construction of the theoretical framework was conducted with specialized literature from scientific articles and books related to the research topic. The type of research is mixed (qualitative-quantitative), the methods applied to obtain the results were the inductive, deductive and analytical methods, among the research techniques an interview was carried out and the internal control questionnaire was made to the personnel in charge of the accounting area, as well as the review of registered documents. With the evaluation of the internal control, a confidence level of 89.71% and a risk of 10.29% was obtained, with the findings found, a final report was presented where recommendations are established in order to improve compliance with tax regulations to the tax process and the presentation of the tax obligations of the company Agrícola Guamán.